2009
DOI: 10.1375/twin.12.4.381
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation Into Etiological Pathways of DCD and ADHD Using a Monozygotic Twin Design

Abstract: W e previously described a co-twin control design using questionnaire data on monozygotic twins discordant and concordant for developmental coordination disorder (DCD) and attention deficit hyperactivity disorder (ADHD). Our results suggested that DCD and developmental ADHD had different causal pathways, and that second-born twins were at higher risk for oxygen perfusion problems than first-born twins. In the current study we further explored our findings using DNA confirmed zygosity and assessments of 4 femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 59 publications
0
15
0
4
Order By: Relevance
“…As noted by Martin et al (2010) , a variety of neurological aetiologies have been suggested for DCD, including pre-, peri-, and post-natal complications ( Kaplan and Sadock, 2007 ; Pearsall-Jones et al, 2009 ), perceptuo-motor organization ( Lord and Hulme, 1988 ), and parietal lobe dysfunction ( Wilson et al, 2004 ). However, as Vaivre-Douret et al (2016) emphasize, the etiology of DCD appears confused on account of the umbrella term of motor dysfunction.…”
Section: Developmental Coordination Disorder (Dcd)mentioning
confidence: 99%
“…As noted by Martin et al (2010) , a variety of neurological aetiologies have been suggested for DCD, including pre-, peri-, and post-natal complications ( Kaplan and Sadock, 2007 ; Pearsall-Jones et al, 2009 ), perceptuo-motor organization ( Lord and Hulme, 1988 ), and parietal lobe dysfunction ( Wilson et al, 2004 ). However, as Vaivre-Douret et al (2016) emphasize, the etiology of DCD appears confused on account of the umbrella term of motor dysfunction.…”
Section: Developmental Coordination Disorder (Dcd)mentioning
confidence: 99%
“…Lichtenstein et al . found that DCD may have a genetic component, and also perinatal oxygen perfusion problems are associated with the disorder .…”
Section: Introductionmentioning
confidence: 99%
“…The remaining variance in coordination difficulty was largely due to non-shared environmental influences, and future research focused on identifying these environmental factors may inform targeted clinical and resilience interventions. These factors might include reduced physical activity, as reported in both adults (Hill and Brown, 2013) and children with DCD (Rivilis et al, 2011), unemployment in adults (Kirby et al, 2013 and pre-and perinatal complications (Pearsall-Jones et al, 2008;Pearsall-Jones et al, 2009). The impact of environmental influences on coordination may also happen via epigenetic mechanisms, which involve changes in gene expression that play a role in a range of neurological disorders (Jakovcevski and Akbarian, 2012;Urdinguio et al, 2009) and these processes should be explored in future studies.…”
Section: Discussionmentioning
confidence: 99%